2014
DOI: 10.1103/physrevc.89.044905
|View full text |Cite
|
Sign up to set email alerts
|

Transverse-energy distributions at midrapidity inp+p,d+Au, andAu+Aucollisions at

Abstract: Measurements of the midrapidity transverse energy distribution, dET /dη, are presented for p+p, d+Au, and Au+Au collisions at √ s N N = 200 GeV and additionally for Au+Au collisions at √ s N N = 62.4 and 130 GeV. The dET /dη distributions are first compared with the number of nucleon participants Npart, number of binary collisions N coll , and number of constituent-quark participants Nqp calculated from a Glauber model based on the nuclear geometry. For Au+Au, dET /dη /Npart increases with Npart, while dET /dη… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 121 publications
9
105
0
Order By: Relevance
“…One possible explanation of the differences is that the corrections for the CMS calorimetry measurement are determined by Monte Carlo [30], while the corrections for the ALICE measurement are mainly data driven. PHENIX [28] reported that while dE T /dη scaled by N part has a pronounced centrality dependence, as seen in Fig. 8, dE T /dη scaled by the number of constituent quarks, N quark , dE T /dη / N quark /2 shows little centrality dependence within the systematic uncertainties for collisions at √ s NN = 62.4-200 GeV.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…One possible explanation of the differences is that the corrections for the CMS calorimetry measurement are determined by Monte Carlo [30], while the corrections for the ALICE measurement are mainly data driven. PHENIX [28] reported that while dE T /dη scaled by N part has a pronounced centrality dependence, as seen in Fig. 8, dE T /dη scaled by the number of constituent quarks, N quark , dE T /dη / N quark /2 shows little centrality dependence within the systematic uncertainties for collisions at √ s NN = 62.4-200 GeV.…”
Section: Resultsmentioning
confidence: 78%
“…[58] and assuming each participating nucleon has an effective transverse radius of R = (σ inel NN /4π ) 1/2 = 0.71 fm results in A = 162.5 fm 2 for central collisions (b = 0 fm). This is equivalent to a transverse overlap radius of R = 7.19 fm, which is close to the value of 7.17 fm often used in estimates of energy densities using a Woods-Saxon distribution to determine the effective area [28,64]. The centrality dependence of A is obtained by assuming it scales as (σ Fig.…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…However, with increased energy, and considering mid-rapidity particle production the linearity is violated. The "number of participant quark" model appears to be a more complete description of the underlying processes [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%